Peranan Intrinsic Value terhadap Motivasi Belajar pada Mahasiswa di Jabodetabek - Riana Sahrani; Hody Denilson; Willy Tasdin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Education is the learning of knowledge, skills, and habits of a group of people that are passed down from one generation to the next through teaching, training, or research. Education often occurs under the guidance of others, but is also possible autodidactically. The etymology of the word Education comes from the Latin